Semiotika Serat Wirid Agem Dalem Nata: Laku Batin Raja Pakubuwana X dalam Membangun Kekuatan Spiritual Kekuasaan Jawa - Dini Frida Handayani; Yusro Edy Nugroho (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
This research explains the Serat Wirid Agem Dalem Nata manuscript as an inner practice of Pakubuwana This research uses Roland Barthes' semiotic approach which is applied in double significance. The manuscript contains wird and hizib, stating that the practitioner is Susuhunan Pakubuwana Through content analysis and reading the five Barthesian codes, in this text we found a signifying relationship that the meaning of reading the wirid emphasizes the king's spirituality, on the other hand it acts as a legitimation of the ideology of government. This can be seen from the contents of the prayer text by the Javanese king for the prosperity of the people and protection for himself. Ideologically, this text, when read in the 20th century, produces the meaning of Javanese political symbols which were maintained amidst the pace of colonialism and social revolution. This gives rise to a new paradigm that complements the historical figure of Susuhunan Pakubuwana Keywords: Pakubuwana X, Serat Wirid Agem Dalem Nata, Laku Batin, Semiotics